Hepcidin and ferritin levels as markers of immune cell activation during septic shock, severe COVID-19 and sterile inflammation - Hortová-Kohoutková, Marcela; Skotáková, Monika; Onyango, Isaac G.; Slezáková, Miriam; Panovský, Roman; Opatřil, Lukáš; Slanina, Peter; De Zuani, Marco; Mrkva, Ondřej; Andrejčinová, Ivana; Lázničková, Petra; Dvončová, Martina; et al. (Frontiers in Immunology, 2023)
Major clinically relevant inflammatory events such as septic shock and severe COVID-19 trigger dynamic changes in the host immune system, presenting promising candidates for new biomarkers to improve precision diagnostics and patient stratification. Hepcidin, a master regulator of iron metabolism, has been intensively studied in many pathologies associated with immune system activation, however these data have never been compared to other clinical settings. Thus, we aimed to reveal the dynamics of iron regulation in various clinical settings and to determine the suitability of hepcidin and/or ferritin levels as biomarkers of inflammatory disease severity. To investigate the overall predictive ability of hepcidin and ferritin, we enrolled the patients suffering with three different diagnoses – in detail 40 patients with COVID-19, 29 patients in septic shock and eight orthopedic patients who were compared to nine healthy donors and all cohorts to each other. We showed that increased hepcidin levels reflect overall immune cell activation driven by intrinsic stimuli, without requiring direct involvement of infection vectors. Contrary to hepcidin, ferritin levels were more strongly boosted by pathogen-induced inflammation – in septic shock more than four-fold and in COVID-19 six-fold in comparison to sterile inflammation. We also defined the predictive capacity of hepcidin-to-ferritin ratio with AUC=0.79 and P = 0.03. Our findings confirm that hepcidin is a potent marker of septic shock and other acute inflammation-associated pathologies and demonstrate the utility of the hepcidin-to-ferritin ratio as a predictor of mortality in septic shock, but not in COVID-19.